Experiences of Suicide Attempt Survivors in Nepal: A Qualitative Study - Sharma, Pujan; Raut, Raju (Journal of Manmohan Memorial Institute of Health Sciences, 2026)
Introduction: Suicide attempt are complex phenomenon which is influenced by psychological, social and cultural factors. It affects both the individual and society as a whole. Despite the growing incidence, there is limited qualitative research addressing the experiences of suicide survivors and how they understand, perceive and interpret their experiences. Method: A qualitative thematic analysis research design was used among 14 participants who survived suicide attempts. A purposive sampling technique was employed to select participants who had direct experience of surviving a suicidal attempt. Semi structured face-to-face interviews using an interview guide developed from the study objectives and relevant literature. Thematic analysis was done data organization , coding were performed using NVivo software. Themes were generated from participants’ experiences. Key domains identified included precipitating factors, cognitive and emotional states, social and relational dynamics and behavioral patterns. Result: The study revealed seven key themes representing the major problems experienced by the participants. These themes are interpersonal conflict, emotional distress, cognitive distortion, social isolation, acute stressor, barrier to help seeking behavior, coping mechanism and post attempt reflection. Participants in the study said they felt extremely sad and hopeless and it was even worse when their family and friends did not understand them. A lot of people said they did not want to ask for help because they were afraid of what others would think of them. Some people said that talking to someone at the hospital after they got hurt really helped them feel better and understood. Hospital-based psychological counseling was reported as beneficial in reducing distress and promoting hope among participants. Conclusion: This study emphasized the importance of early psychological intervention, family involvement, and culturally sensitive mental health care in suicide prevention. By focusing on suicide survivor’s experiences, the research provides insights for policymakers, practitioners, and mental health advocates working to reduce suicide rates in Nepal.